STRATEGIC MANAGEMENT OF DIGITALIZATION FOR POWER DISTRIBUTION SYSTEM RELIABILITY INDEX: DEVELOPMENT AND IMPLEMENTATION OF A DEV C++ - Rio Afrianda (CV. ADIBA AISHA AMIRA, 2025)
PT PLN (Persero) is the state-owned company responsible for electricity supply in Indonesia, with a key mandate to ensure reliable power distribution that meets established service quality standards. This study aims to analyze outage events as a basis for reducing blackout frequency and minimizing customer complaints. Improved reliability not only decreases service interruptions but also enhances system efficiency and optimizes energy transfer. The research employs a qualitative approach by analyzing reliability indices, specifically SAIDI (System Average Interruption Duration Index) and SAIFI (System Average Interruption Frequency Index), supported by the development of an application using the C programming language, known for its simplicity, flexibility, and widespread use. The findings show that SAIDI analysis provides insights for improving subsystems, including components and equipment, while SAIFI highlights opportunities to enhance operational procedures for outage management and repair acceleration. The calculation results indicate that in 2022, the average SAIDI was 3.9152 hours/customer/year, and the average SAIFI was 0.0896 interruptions/customer/year. These results demonstrate the potential of integrating digital tools to strengthen strategic reliability management in power distribution systems.